2021
DOI: 10.2147/dmso.s300460
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices and Its Association with Microvascular Complications Among Type 2 Diabetes Mellitus Patients in Northeast Ethiopia: A Cross-Sectional Study

Abstract: Purpose Platelet indices have been shown to be associated with complications of diabetes mellitus (DM). However, the clinical relevance of platelet indices for assessing the risk of being microvascular complications among patients with DM is largely overlooked. Hence this study aimed to determine the association of platelet indices with microvascular complications among type 2 DM patients. Patients and Methods A hospital-based cross-sectional study was conducted among 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
4
0
3
Order By: Relevance
“…В стационарном режиме эти более крупные тромбоциты выделяют больше тромбоксана-2 (активатора агрегации тромбоцитов). К более крупным и метаболически активным относятся молодые тромбоциты и зрелые отросчатые тромбоциты в состоянии активации [33][34][35][36][37].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…В стационарном режиме эти более крупные тромбоциты выделяют больше тромбоксана-2 (активатора агрегации тромбоцитов). К более крупным и метаболически активным относятся молодые тромбоциты и зрелые отросчатые тромбоциты в состоянии активации [33][34][35][36][37].…”
Section: Discussionunclassified
“…Чем выше будут показатели IPF, P-LCR, MPV, PDW, тем больше в крови пациента более крупных и молодых тромбоцитов, которые отражают более высокий уровень метаболической, ферментативной и функциональной активности. Молодые и крупные тромбоциты содержат больше -гранул, максимально обогащенных медиаторами [35,39]. Таким образом, чем выше будут показатели PLT, IPF, P-LCR, MPV, PDW, тем более биологически активной будет получаемая БоТП.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Two hundred eighty-five patients were evaluated in our research, and proteinuriawas seen in 114 patients (40%).This is per other studies, which have also shown proteinuria as a common complication. [11][12][13][14][15] Multiple studies have been performed worldwide to know the exact prevalence of proteinuria in diabetic patients at the time of presentations. In one study, it appeared to be25.6% [16], while in another study, it was 57.44%.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between increased PDW and MPV with diseases connected to endothelial dysfunction including diabetes, coronary artery disease [CAD], and cancer has been shown in numerous studies [4] . In some recently published research, patients with diabetic nephropathy had higher platelet indices such as PDW and MPV [5] .…”
Section: Introductionmentioning
confidence: 93%